The project of inclusive democracy : no longer a toddler - Gezerlis, Alexandros (Quilmes, Argentina : Universidad Nacional de Quilmes, 2004)
Inclusive Democracy is the project for direct political democracy, economic democracy (beyond the confines of the market economy and state planning), as well as democracy in the social realm and ecological democracy. In short, Inclusive Democracy is a form of social organisation which re-integrates society with economy, polity and nature. The concept of Inclusive Democracy is derived from a synthesis of two major historical traditions: the classical democratic and the socialist. It also encompasses radical green, feminist, indigenous and liberation movements in the South. From the Inclusive Democracy perspective the world is in a multidimensional crisis, caused by the concentration of power in the hands of various elites, as a result of the establishment of the economic system of market/growth economy, its political complement in the form of representative democracy, and the related forms of hierarchical structures. Inclusive Democracy is therefore not seen as a utopia but as probably the only way out of the present crisis.
Descripción basada en metadatos suministrados por el editor y otras fuentes.
Descripción basada en Revista theomai, n. 10 (segundo semestre 2004), P. 11 sin numerar.
Recurso electrónico. Santa Fe, Arg.: elibro, 2023. Disponible vía World Wide Web. El acceso puede estar limitado para las bibliotecas afiliadas a elibro.
Keywords: Democracia inclusiva; Artículos electrónicos.